How to resist fear. ETA terrorism and Basque Socialism, 1995-2011 - Sara Hidalgo García de Orellán (Culture & History Digital Journal)
The aim of this paper is to show the emotional impact of ETA terrorism on the PSE-EE militancy during the years of the socialisation of suffering, 1995-2011. To do so, we will use the theoretical-methodological tools provided by the history of emotions. It will be seen how emotional suffering greatly shaped the socialist experience in this period, whose experience has been codified with elements such as pressure and social isolation, threats and aggressions, or the lack of freedom of movement (due to the obligation to carry an escort). This emotional suffering was a constitutive part of the culture of resistance that Basque socialism redefined at this time -and linked to the resistance carried out by the socialists in the years of the Franco dictatorship-. In this redefinition, the strategies to overcome fear were the political commitment, anger, and courage, a feeling of pride for fighting against ETA, and strong group solidarity. These elements partly explain why the PSE-EE could survive and why its members continued to carry out their political work.